Flood Risk Assessment in the Sungai Senggarang Catchment Using InfoWorks ICM - Rahmat, Siti Nazahiyah; Alfi Rahmi (International Journal of Sustainable Construction Engineering and Technology, 2025)
Flooding poses a significant threat to low-lying areas, affecting lives, infrastructure, and ecosystems, and is further intensified by climate change, urbanization, and extreme weather. This study investigates the Sungai Senggarang catchment in Batu Pahat, Johor, using InfoWorks Integrated Catchment Modelling (ICM), a hydrodynamic software that generates 2D floodplain models to develop flood maps. The area, known for its susceptibility to flooding, is predominantly low-lying and lies downstream of the region's waterways, making it crucial to understand flood behavior and associated risks. The flood map was developed by integrating a 3D ground model from GIS with hydrological and hydraulic parameters of the study area. Detailed survey data of Sungai Senggarang, together with historical rainfall records from the 2006/2007 major flood event, were used in the simulation. Flood maps were produced for both current (2016) and projected future (2030) land use scenarios, simulated using design storms with average recurrence intervals (ARIs) of 20, 50, and 100 years for a 6-hour critical storm. Results indicated increased runoff and flood impacts under future development scenarios. The software's effectiveness was validated by the close similarity between the simulated present-day 50-year ARI flood map and the historical 2006/2007 flood event. This study demonstrates that advanced flood modelling software can provide critical insights into the extent and severity of flooding under varying development and climate conditions, supporting the integration of hydrological, hydraulic, and topographic data for more effective flood risk management.